Effects of monoglycerides on aeration enhancement during industrial production of cakes and ice creams - Lee, Lai Yee (2017)
Monoglycerides are the most commonly used food emulsifiers, as crumb softener, emulsion stabiliser and aeration enhancer. Putting aside the product composition, the main variations in monoglycerides are the fatty acid composition and degree of unsaturation. This study aimed to evaluate the aeration enhancement effects of monoglycerides in bakery and dairy applications in view of the bakery manufacturers perception that monostearin (C18) performs better than monopalmitin (C16), and the fact that the blend of saturated monoglycerides and polysorbate 80 have been used historically in ice creams formulations instead of unsaturated monoglycerides. Four types of monoglycerides from different raw materials (different C16 to C18 ratio) were used to make cake gel, assessed and applied into sponge cakes and found to perform equally well in terms of batter aeration and final cake volume and softness. Two saturated and three unsaturated monoglycerides were applied in ice creams. The mix and ice creams were evaluated for aeration performances through quantification of fat globules size distribution, meltdown resistance and heat shock stability. A slightly higher degree of unsaturation (17 – 25 g I2/100g compared to 10 – 17 I2/100g) gave better meltdown and heat shock resistances. Both unsaturated monoglycerides performed better than saturated monoglycerides and when it was dosed in combination with polysorbate 80. The meltdown rate between the saturated and unsaturated monoglycerides was 0.17 – 0.26% per min and 0.12 – 0.19% per min respectively. It was also concluded that ice creams with meltdown rate below 0.2% per min could be defined to have good meltdown resistance performance. Monoglycerides are added into ice cream through texturising system in the ice cream industry. Although unsaturated monoglycerides gives better aeration performances in general, its use is carefully evaluated as it could lead to change of textural and organoleptic properties of the ice cream of which some manufacturers find it undesirable. The other quality concerns and challenges faced by the ice cream manufacturers in Asia Pacific region include excessive mix viscosity, poor heat shock resistances, product shrinkage and ice crystals development over time.